Hubungan Penggunaan Rekam Medis Elektronik (RME) dengan Kepuasan Petugas Kesehatan di RSU Imelda Pekerja Indonesia - Simanjuntak, Esraida; Sitorus, Mei Sryendang; Lubis , Siti Permata Sari; Sihite, Geovani Arta (Universitas Hang Tuah Pekanbaru, 2025)
The level of feeling experienced by patients as a result of the performance of the health services they receive after comparing it with their expectations is known as patient satisfaction. The purpose of this study was to illuminate how the satisfaction of health workers with the use of Electronic Medical Records (EMR) is poured into the dimensions of content, chimney, format, ease of use, and timeliness at RSU Imelda Buruh Indonesia Medan. Based on the criteria that have been set, this study uses a descriptive method with a quantitative approach. A total sample of 62 people was taken from the population. Observation sheets and questionnaires are research tools. This study found that the use of EMR on the variables of content, precision, ease of use, and timeliness is met with the satisfaction of health workers at RSU Imelda Buruh Indonesia. However, the variable format does not satisfy satisfaction, There is no relationship between the use of EMR in the format variable and the satisfaction of health workers at RSU Imelda Buruh Indonesia. It It is recommended that there are more detailed regulations regarding the use of RME so that the use of RME at the Imelda Buruh Indonesia Hospital can be maximized and that there is a need to re-socialize the regulations on the accuracy of filling in RM so that RM recording by PPA is more complete and accurate so that the quality of reports as RME output can be improved.